Emergence and Epidemiology of Bovine Babesiosis Due to Babesia divergens on a Northern German Beef Production Farm - Springer, Andrea; Höltershinken, Martin; Lienhart, Fabienne; Ermel, Sandra; Rehage, Jürgen; Hülskötter, Kirsten; Lehmbecker, Annika; Wohlsein, Peter; Barutzki, Dieter; Gietl, Christine; Baumgärtner, Wolfgang; Hoedemaker, Martina; et al. (Frontiers in Veterinary Science, 2020)
Babesia divergens, transmitted by the tick Ixodes ricinus, is the most common cause of bovine babesiosis in northern Europe and plays a role as a zoonotic pathogen. However, several studies have indicated a decline of B. divergens prevalence in Europe during the last decades. Here, we investigate the epidemiology of bovine babesiosis on a beef production farm in northern Germany, which had not been affected by babesiosis until an initial outbreak in 2018. In June 2018, 21 adult cattle died, showing classical symptoms of babesiosis. Babesia divergens merozoites were detected in blood smears of clinically affected animals and the species was confirmed by PCR and sequencing of a part of the 18S rRNA gene. In 2018, screening of the farm’s entire stock by PCR revealed that Babesia-positive animals were present in only one of five herds grazing on different pastures. In the following year, further babesiosis cases occurred in multiple herds. In March 2020, 95 cattle were tested for anti-B. divergens antibodies and 36 of them (37.89%) had positive titres. To investigate the local Babesia prevalence in ticks, 1430 questing I. ricinus ticks (555 larvae, 648 nymphs, 227 adults) were collected on the farm’s pastures and subjected to PCR for Babesia detection. Babesia divergens DNA could not be detected, but Babesia microti showed an overall prevalence of 0.49% (7/1430; 0.88% [2/227] of adult ticks, 0.77% [5/648] of nymphs, 0.00% [0/555] of larvae). Babesia venatorum was detected in 0.42% (6/1430) of ticks (0.44% [1/227] of adult ticks, 0.77% [5/648] of nymphs, 0.00% [0/555] of larvae) and B. capreoli in 0.07% (1/1430) of ticks (0.00% [0/227] of adult ticks, 0.15% [1/648] of nymphs, 0.00% [0/555] of larvae). Despite the fact that no B. divergens-positive ticks were found, the collected data suggest a geographical spread of the pathogen on the farm. Bovine babesiosis remains a disease of veterinary importance in Europe and may cause considerable economic losses when (re-)emerging in non-endemic areas, especially as awareness for the disease among veterinarians and farmers declines.